FKEPG-LIMS : Fakulti Kejuruteraan Elektrik Kampus Pasir Gudang Lab Inventory Management System - Yasmin Abdul Rahman, Farah; Kasuan, Nurhani; Hisham Mat Saat, Ezril; Hasliza Abdul Rahman, Noor; Iqtiyan Ilham, Nur; Noor Suhana Jamil, Siti (International Journal of Engineering and Technology, 2018)
Information are the most valuable commodity in the modern era. In today’s lifestyle, society are virtually swarmed with a lot of            information that cannot be misplaced or vanished. This study presents a development of web-based lab inventory management system that is used to record, manage and retrieve the lab equipment and components in Fakulti Kejuruteraan Elektrik Kampus Pasir Gudang namely FKEPG-LIMS. The main purpose of this study is to assist faculty members to view and keep track all the available lab       equipment that have been purchased. The users can be classified as the Faculty Head, lab technicians, lecturers and students. The       database is developed using MySQL and the HTML script written in PHP and Adobe Dreamweaver used design the web interface. The research has successfully demonstrated the feasibility of FKEPG-LIMS in managing and storing all the information. The stored         information can also be retrieved, edited and deleted. The developed lab inventory management system will benefits users by providing fast and precise solution in inventory management.